Humanizing human capital : invest in your people for optimal business returns - Charas, Solange; Lupushor, Stela (Ascent Audio, 2022)
In Humanizing Human Capital, Solange Charas, PhD, and Stela Lupushor reframe traditional HR practices into a future-forward strategy to optimize human capital. Charas and Lupushor shift decision-making about people from a gut sense to an evidence-based approach-a critical and much-needed departure from the cross-your-fingers-and-hope-for-the-best approach of most traditional HR programs today. Learn how to quantify and manage human capital in order to future-proof your financial returns. Humanizing Human Capital reveals a step-by-step method to apply analytics approaches to human capital while anticipating inevitable changes in the workforce landscape. This will enable human capital professionals to generate positive outcomes for all stakeholders and allow management to make decisions that work for the entire enterprise. Through dozens of case studies, real-world situations, and twenty invaluable business principles, you will learn to: adopt a best-evidence versus best-practice approach to decision-making; shift your thinking so that you view human capital as a crucial investment rather than as a sunk cost; balance human capital analytics with the more human-centric elements of people management; increase value for all key stakeholders; and utilize methods to measure and optimize human capital efficiency, increasing your ROI.